2014
DOI: 10.1111/bju.12579
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ease of perinephric fat dissection at time of open partial nephrectomy using preoperative fat density characteristics

Abstract: ObjectiveTo predict the ease of perinephric fat surgical dissection at the time of open partial nephrectomy (OPN) using perinepheric fat density characteristics as measured on preoperative computed tomography (CT). Patients and MethodsIn all, 41 consecutive OPN patients with available preoperative imaging and prospectively collected dissection difficulty assessment were identified. Using a scoring system that was adopted for the purposes of this study, the genitourinary surgeon quantified the difficulty of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 15 publications
0
51
1
2
Order By: Relevance
“…The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12]. Since Asians tend to have higher percentages of body fat than Caucasians do at equivalent BMIs [7,8], it could be supposed that the incidence of APF in Asians is close to that in Caucasians, in spite of the difference in their mean BMIs.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12]. Since Asians tend to have higher percentages of body fat than Caucasians do at equivalent BMIs [7,8], it could be supposed that the incidence of APF in Asians is close to that in Caucasians, in spite of the difference in their mean BMIs.…”
Section: Discussioncontrasting
confidence: 85%
“…In other studies, radiographic features have been said to be independent predictors of APF [12,13]. The MAP score has broad utility because it can be calculated based on both computed tomography and T1-weighted magnetic resonance imaging [6].…”
Section: Discussionmentioning
confidence: 99%
“…APF can be a frustrating surgical variable encountered during PN that can limit mobilization of the kidney and isolation of the kidney tumor, and its removal can often lead to tearing of the renal capsule [14]. Experienced and respected partial nephrectomists have openly commented on the need for a model that predicts the risk of encountering intraoperative APF [7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we did not include an analysis of the impact of APF on the outcomes of RAPN. In the only studies thus far examining APF along with operating room variables, APF was shown to predict longer operating room times for PN [14,19]. APF alone may be a surrogate for surgical complexity and may push less experienced partial nephrectomists to select an alternative approach, such as an open PN or an ablation, for treating small renal masses in these particular patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation